2003
DOI: 10.1093/jpepsy/jsg030
|View full text |Cite
|
Sign up to set email alerts
|

Stable Preterm Infants Gain More Weight and Sleep Less after Five Days of Massage Therapy

Abstract: Healthy, low-risk preterm infants gained more weight and slept less with just 5 days of massage, in contrast to 10 days in previous studies. Results support the continued use of massage as a cost-effective therapy for medically stable preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
4
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 46 publications
9
98
4
5
Order By: Relevance
“…The increased weight gain shown by the moderate pressure massage group is consistent with increased weight gain in many studies on both preterm infants Dieter, Field, Hernandez-Reif, Emory & Redzepi, 2003;Field et al, 1986) and full-term infants (Field, Hernandez-Reif, Diego, Feijo, Vera & Gil 2004;Goldstein-Ferber, 2004;Moyer-Mileur, Brunstetter, McNaught, Gill & Chan, 2000).…”
Section: Discussionsupporting
confidence: 62%
“…The increased weight gain shown by the moderate pressure massage group is consistent with increased weight gain in many studies on both preterm infants Dieter, Field, Hernandez-Reif, Emory & Redzepi, 2003;Field et al, 1986) and full-term infants (Field, Hernandez-Reif, Diego, Feijo, Vera & Gil 2004;Goldstein-Ferber, 2004;Moyer-Mileur, Brunstetter, McNaught, Gill & Chan, 2000).…”
Section: Discussionsupporting
confidence: 62%
“…Infants receiving M/KS do not consume or retain more calories than controls, as ours and previous studies have shown similar caloric intake patterns between the groups. 2,3,6,7 Similarly, M/KS infants do not appear to conserve more calories by spending more time in the sleep state, because studies have actually shown increased arousal in massaged infants compared to controls. 2,3 Thus, it remains that the increase in weight gain is most likely related to hormonal alterations or changes in basal metabolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have suggested that massage therapy with KS may have positive effects on preterm infants including greater weight gain, [1][2][3][4][5][6][7] improved bone mineralization, 8 earlier hospital discharge, [1][2][3] and more optimal behavioral and motor responses 2-4,9,10 compared to controls. However, there is inconsistency of these findings across studies and methodological concerns with previous trials have led some authors to caution widespread and routine use of preterm infant massage.…”
Section: Introductionmentioning
confidence: 99%
“…182,183 Gentle human touch is perceived as a simpler, less arousing and more easily implemented form of human touch, and may be tolerated by smaller preterm infants, 184 although selective use of infant massage does appear safe. 185 Massage in preterm infants has shown significant [186][187][188][189][190][191][192] or trends toward 193,194 improved weight gain, and decreased length of stay. 187,192 Weight gain may be mediated by increased nutritional intake 195 and/or through increased vagal activity and gastric motility.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%
“…202 Massage has been associated with a shift from less total sleep, towards more periods of drowsiness 188 and post-massage sleep may be increased. 193 The use of gentle touch has been associated with lower levels of AS, motor activity and behavioral distress, but no differences were seen in weight gain or behavioral organization.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%